Ketorolac Administration After Colorectal Surgery Increases Anastomotic Leak Rate: A Meta-Analysis and Systematic Review - Chen, Wen; Liu, Jing; Yang, Yongqiang; Ai, Yanhong; Yang, Yueting (Frontiers in Surgery, 2022)
Objective This meta-analysis aimed to evaluate whether ketorolac administration is associated with an increased anastomotic leak rate after colorectal surgery. Methods The literature was searched using the Web of Science, Embase, and PubMed databases, and the search ended on May 31, 2020. The Newcastle–Ottawa Scale was used to assess methodological quality. Statistical heterogeneity was assessed using the Chi-square Q test and I2 statistics. Subgroup analysis was performed, and Egger's test was used to assess publication bias. Results This meta-analysis included seven studies with 400,822 patients. Our results demonstrated that ketorolac administration after surgery increases the risk of anastomotic leak [OR = 1.41, 95% CI: 0.81–2.49, Z = 1.21, P = 0.23]. Low heterogeneity was observed across these studies (I2 = 0%, P = 0.51). The results of subgroup analysis showed that the use of ketorolac in case–control and retrospective cohort studies significantly increased the risk of anastomotic leak (P < 0.05). Furthermore, the subgroup analysis revealed that ketorolac use increased anastomotic leak rate in patients in the United States and Canada, and ketorolac plus morphine use did not increase anastomotic leak rate in Taiwanese patients (P < 0.05). No significant publication bias was observed (P = 0.126). Moreover, the analysis of risk factors related to anastomotic leak rate indicated that the total use of ketorolac did not increase the risk of anastomotic leak similar to the control group (P > 0.05). Conclusion The meta-analysis indicates that the use of ketorolac increases the risk of anastomotic leak after colorectal surgery. Systematic Review Registration PROSPERO, identifier CRD42020195724.